Serum BDNF levels as a potential prognostic marker for functional recovery in stroke: Preliminary findings from a prospective observational study - Seyoung Shin; Heegoo Kim; Dae Hyun Kim; Won Hyuk Chang (PLoS ONE, 2026)
Brain-derived neurotrophic factor (BDNF) crosses the blood-brain barrier and may serve as a marker of neuroplasticity. This study evaluated whether serum levels of mature BDNF, proBDNF, and matrix metalloproteinase-9 (MMP-9) can predict functional recovery after stroke. In this prospective observational study, 93 patients with unilateral stroke and motor impairment were recruited. Clinical, and demographic data, as well as serum levels of mature BDNF, proBDNF, and MMP-9 were collected. Functional assessments measuring stroke severity, cognition, motor function, balance, and mood were conducted at three timepoints: after acute care (T0), 2 weeks post-rehabilitation (T1), and 3 months post-onset (T2). Mature BDNF significantly decreased from T0 to T2 (p = 0.003), while proBDNF remained stable. MMP-9 declined consistently across timepoints (p < 0.001). MMP-9 levels at baseline differed by BDNF genotype (p < 0.05). However, none of the biomarkers independently predicted functional recovery. Functional outcomes improved significantly over time (p < 0.001), with baseline functional scores being the strongest predictors at T1 and T2. Although these biomarkers were not independent predictors of recovery, their longitudinal trajectories may reflect underlying neurobiological recovery mechanisms during rehabilitation, although their prognostic utility remains inconclusive.